Shifts in mosquito diversity and abundance along a gradient from oil palm plantations to conterminous forests in Borneo - Young, Katherine I.; Buenemann, Michaela; Vasilakis, Nikos; Perera, David; Hanley, Kathryn A. (esa, 2021)
Deforestation precipitates spillover of enzootic, vector-borne viruses into humans, but specific mechanisms for this effect have rarely been investigated. Expansion of oil palm cultivation is a major driver of deforestation. Here, we demonstrate that mosquito abundance decreased over ten stepwise distances from interior forest into conterminous palm plantations in Borneo. Diversity in interior plantation narrowed to one species, Aedes albopictus, a potential bridge vector for spillover of multiple viruses. A. albopictus was equally abundant across all distances in forests, forest-plantation edge, and plantations, while A. niveus, a known vector of sylvatic dengue virus, was found only in forests. A. albopictus collections were significantly female-biased in plantation but not in edge or forest. Our data reveal that the likelihood of encountering any mosquito is greater in interior forest and edge than plantation, while the likelihood of encountering A. albopictus is equivalent across the gradient sampled from interior plantation to interior forest.